EVALUASI KETERAMPILAN LABORATORIUM MAHASISWA MENGGUNAKAN ASESMEN KEGIATAN LABORATORIUM BERBASIS KOMPETENSI PADA PELAKSANAAN PRAKTEK PENGALAMAN LAPANGAN (PPL) - Djohar Maknun (Holistik, 2012)
This research is evaluative, aims to measure students’ skills in conducting credible form of science labs in science learning experiences at the practice field (PPL). This research is the development of a quasi-experimental approach to science majors Tadris Biology IAIN Shekh Nurjati Cirebon. The method used is a preliminary survey and assessment of competency-based laboratory credible form. The results of this study are: first, the lab’s skills for the competence of calibration, maintain, record and process data are lacking. Second, the factors supporting the development of student’s skills in operating lab such as the lab, instrument, materials lab and lab guides, and currently inhibiting factor is the lack of practice time, limited equipment and damage to equipment.